The Electricity Consumption and Economic Growth Nexus in Pakistan: A New Evidence - Syed Muhammad Atif; Muhammad Wasif Siddiqi (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2010)
This study examines the Granger causality between electricity consumption and Gross Domestic Product (GDP) for Pakistan using annual data covering the period 1971 to 2007. Augmented Dickey-Fuller test and Phillips-Perron test reveal that both the series, after logarithmic transformation, are non-stationary and individually integrated at order one. Engle and Granger Cointegration test exhibits the absence of long-run relationship among the variables. Two tests of causality, standard Granger Causality test and Modified WALD test (T-Y test) affirm the existence of unidirectional Granger causality from electricity consumption to economic growth without any feedback effect. Therefore, an immediate effort to increase electricity availability is required and energy conservation policies are supposed to halt the economic growth.
Keywords: C32; O20; Q43; 330; Economic Growth; Electricity Consumption; Toda-Yamamoto; Pakistan; Economic Growth; Electricity transmission